2006
DOI: 10.1002/bit.21262
|View full text |Cite
|
Sign up to set email alerts
|

Gene transcription acceleration: main cause of hepatitis B surface antigen production improvement by dimethyl sulfoxide in the culture of Chinese hamster ovary cells

Abstract: The production and specific productivity of hepatitis B surface antigen (HBsAg) in recombinant Chinese hamster ovary (CHO) cells were increased by 81% and threefold, respectively, when supplemented with 1.5% dimethyl sulfoxide (DMSO) in the culture medium. To investigate the mechanism of DMSO effect on HBsAg production improvement, HBsAg mRNA level was measured by real-time PCR. HBsAg mRNA was increased by about 1.5-fold at 1.5% DMSO. The increase could derive from the increase of HBsAg gene copy number, the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…10,11 Thus, these results and the present study on the rchIL-12/eGFP protein suggests that specific gene expression patterns after transfection may depend on the host cell targets. In a study on the effect of DMSO on transcription level of HBsAg gene expression, Wang et al (2006) 19 indicated that some post-translation events, such as the saturation of the secretion pathway, the inhibition of DMSO on HBsAg secretion pathway, and the limitation of post-translation modification of protein, could involve in restriction on the HBsAg secretion. For example, DMSO downregulates HSP70 and ERP57, which play an important role in stabilizing the folding and assembly intermediates of newly synthesized polypeptides.…”
Section: Purification and Bioactivity Assay Of The Fusion Proteinmentioning
confidence: 99%
See 2 more Smart Citations
“…10,11 Thus, these results and the present study on the rchIL-12/eGFP protein suggests that specific gene expression patterns after transfection may depend on the host cell targets. In a study on the effect of DMSO on transcription level of HBsAg gene expression, Wang et al (2006) 19 indicated that some post-translation events, such as the saturation of the secretion pathway, the inhibition of DMSO on HBsAg secretion pathway, and the limitation of post-translation modification of protein, could involve in restriction on the HBsAg secretion. For example, DMSO downregulates HSP70 and ERP57, which play an important role in stabilizing the folding and assembly intermediates of newly synthesized polypeptides.…”
Section: Purification and Bioactivity Assay Of The Fusion Proteinmentioning
confidence: 99%
“…12,15,16 DMSO may have a broad impact on many aspects of gene expression in eukaryotic cell systems. 15,16,19,21 However, little is known about the exact mechanism by which DMSO exerts an effect. It has been demonstrated that the production of hepatitis B surface antigen (HBsAg) in recombinant CHO cells was increased by 81% and the productivity of HBsAg by a single cell was increased by threefold when the culture medium was supplemented with 1.5% DMSO.…”
Section: Purification and Bioactivity Assay Of The Fusion Proteinmentioning
confidence: 99%
See 1 more Smart Citation
“…Bioactive chemicals can target many cellular mechanisms, with inducing upregulation of protein production. A wide variety of molecules have been used to accomplish this, including quinoline thioethers [12], dimethyl sulfoxide [3,7,[13][14][15], and aurintricarboxylic acid [7]. Additionally, broad classes of small molecules including aromatic carboxylic acids, hydroxamic acids, and acetamides have been studied [16].…”
Section: Discussionmentioning
confidence: 99%
“…DMSO induces apoptosis in some cell lines (Marthyn et al 1998) whereas it inhibits cell density-dependent apoptosis of CHO cells (Fiore and Degrassi 1999). DMSO may have a broad impact on many aspects of gene expression in animal cells (Li et al 2006;Liu et al 2001;Wang et al 2007;Sumida et al 2011). DMSO can stimulate CHO cells to synthesize different recombinant proteins .…”
Section: Introductionmentioning
confidence: 97%